Drinking, Diversity, and Discrimination: Campus-Level Factors that Influence Students’ Risk of Experiencing Sexual Assault - Moylan, Carrie A. (Journal of interpersonal violence, 2024)
College students’ individual-level risk factors for sexual assault victimization have been studied for decades, but fewer studies have looked at whether and how campus-level factors, such as campus-level rates of discrimination and campus diversity, might also influence student victimization risk. Identifying these broader factors can inform efforts to develop more effective campus-level sexual assault preventive interventions. We conducted a secondary analysis of data from a large, multi-campus health and well-being survey (N = 309,171 students across 474 US campuses) to explore how campus-level factors shape students’ risk of experiencing sexual assault after accounting for students’ individual-level risk factors. Using mixed-effects logistic regression, we examined the influence of campus-level factors (e.g., campus sexual orientation demographics and gender diversity) on students’ odds of experiencing sexual assault, after accounting for individual risk factors (e.g., sexual and gender minority status). Although some campus characteristics, such as enrollment size, had small significant effects on students’ odds of experiencing sexual assault, we found larger significant effects from aggregated campus-level rates of binge drinking, campus diversity (particularly regarding sexual orientation and gender), and discrimination. These findings suggest that comprehensive campus sexual violence prevention would benefit from strategies that promote safe and inclusive campuses, especially for students with marginalized sexual and gender identities.